2013
DOI: 10.2190/cs.15.3.c
|View full text |Cite
|
Sign up to set email alerts
|

Hitting the Books Again: Factors Influencing the Intentions of Young Adults to Reenroll in College

Abstract: Results from the analyses of data from 463 former college students between the ages of 25 and 34 years old identify those most likely to reenroll in higher education in the near future. Those who intend to reenroll are more likely to be members of minority groups, younger, single, and recently laid-off, have earned more credits, and hold strong beliefs about the value of education. Specific recommendations for strategies and policies through which colleges could motivate former students to reenroll and facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…In the case of the school and college, this comprises students suffering from ADHD, dyslexia, cognitive difficulties, developmental disorders and other learning difficulties (Abikoff et al, 2013;Breaux et al, 2019;Davies et al, 2002;Deng & Xuan, 2009;Evans et al, 2016;Giust & Valle-Riesta, 2017;Green et al, 2011;Janeslätt et al, 2014;Keptner & Rogers, 2019;Kirby et al, 2008;LaCount et al, 2018;Langberg et al, 2013;Lewandowski et al, 2013;Martin et al, 2020;Persson et al, 2017;Prevatt et al, 2017;Reed & Jones, 2021;Reed & Kennett, 2017;Sauvé et al, 2016;Siddiqi & Memon, 2016;Solanto & Scheres, 2021). It is also useful for adult university students who have to combine their studies and work or students from ethnic minorities (Keptner & Rogers, 2019;Meeuwisse et al, 2013;Schatzel et al, 2013).…”
Section: Efficient Time Management and Discourse Of Deviationmentioning
confidence: 99%
“…In the case of the school and college, this comprises students suffering from ADHD, dyslexia, cognitive difficulties, developmental disorders and other learning difficulties (Abikoff et al, 2013;Breaux et al, 2019;Davies et al, 2002;Deng & Xuan, 2009;Evans et al, 2016;Giust & Valle-Riesta, 2017;Green et al, 2011;Janeslätt et al, 2014;Keptner & Rogers, 2019;Kirby et al, 2008;LaCount et al, 2018;Langberg et al, 2013;Lewandowski et al, 2013;Martin et al, 2020;Persson et al, 2017;Prevatt et al, 2017;Reed & Jones, 2021;Reed & Kennett, 2017;Sauvé et al, 2016;Siddiqi & Memon, 2016;Solanto & Scheres, 2021). It is also useful for adult university students who have to combine their studies and work or students from ethnic minorities (Keptner & Rogers, 2019;Meeuwisse et al, 2013;Schatzel et al, 2013).…”
Section: Efficient Time Management and Discourse Of Deviationmentioning
confidence: 99%
“…seminal study discovered that students who reenroll after a disciplinary suspension are more likely to be male than female, have a higher grade point average (GPA) than those who do not reenroll, and tend to have been charged with minor, rather than major, conduct violations. In addition, minorities, younger, single, and recently unemployed students who have earned more college credits, and hold strong beliefs about the value of education, tend to reenroll (Schatzel, Callahan, & Davis, 2013). A brief history of student conduct administration can assist in better understanding how these conclusions were made and how they can be built upon.…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…Scholars have studied other, more general, aspects of students who reenroll. Schatzel, Callahan and Davis (2013) concluded that students who intend to reenroll in college are more likely to be minorities, younger, single, and recently laid-off. They also tended to have earned more credits, and hold strong beliefs about the value of education (Schatzel, Callahan & Davis, 2013).…”
Section: Other Studies On Students Who Reenrollmentioning
confidence: 99%
See 1 more Smart Citation
“…This assertion is supported by Horn, who found that academic integration factors like faculty interactions, participation in study groups, and relationships with advisors were predictive of higher levels of re-enrollment for departing students. Schatzel, Callahan, & Davis (2013) determined that students displaying strong goal commitments (as framed by Tinto, 1993) and measures of academic integration were more likely to return to their schools. Hoyt & Winn (2004) differentiated behaviors of stop-outs to transfer-outs and drop-outs and found that each group emphasized different challenges affecting their ability to remain enrolled (or return).…”
Section: College Stop-out Studentsmentioning
confidence: 99%